Symbiotic interactions on middle Cambrian echinoderms reveal the oldest parasitism on deuterostomes - Iban Goñi; Claude Monnet; Kenneth De Baets; Timothy P. Topper; Sylvie Régnier; Laurenz Schröer; Veerle Cnudde; Peter A. Jell; Sébastien Clausen (Scientific Reports, 2025)
Abstract Biotic interactions are considered as major drivers of evolutionary changes, but their identification in the fossil record is extremely rare and controversial. Based on qualitative and quantitative analyses, we report evidence of a biotic interaction between an echinoderm host and its symbiont, probably a parasitic epibiont, from the Cambrian Wuliuan Stage of Australia. The echinoderm plates bear external outgrowths with a median pit at their distal end. These unusual structures have not been previously documented from Cambrian echinoderms and their lack of consistency across various morphological parameters, supports the interpretation that a biotic interaction generated these unique structures. Perturbations in plate microstructure and the overproduction of skeletal material in specific regions, together with reduced size, negatively impact the host’s growth suggesting a parasitic interaction. This reaction by the echinoderm host may represent the progressive embedment of the invasive epibiont. This record represents the oldest evidence of parasitism among deuterostomes.